Hubungan Asupan Gizi, Pemberian Asi Eksklusif, dan Pengetahuan Ibu dengan Status Gizi (Tb/U) Balita 6-59 Bulan - Bertalina Bertalina; Amelia P.R (Jurnal Kesehatan, 2018)
Stunting prevalence in Indonesia is 37,2%, whereas in Bandar Lampung City is 44,6% and in Kemiling District is 39,6%. This study was to determine the risk factors associated with children nutritional status (TB/U) in Beringin Jaya, Kemiling. This analytical survey research was using cross-sectional design. Population in this study were 1141 toddlers, and 88 as respondents. Cluster Sampling was used to determine the respondents. Data was analyzed Univariate and Bivariate. This research was conducted in Beringin Jaya, Kemiling. The result showed that 19 toddlers (21.6%) were identified stunting and 69 (78.4%) toddlers were normal. There was no correlation between energy intake with nutritional status (TB/U) with p-value=0,175. There was a correlation between protein intake with nutritional status (TB/U) with p-value=0,022. There was no correlation between exclusive breastfeeding and nutritional status (TB/U) with p-value=0.758. There was no correlation between mother’s knowledge of nutritional status (TB/U) with value p-value=1,000. It was suggested that Public Health Centers and Integrated Service Center should improve its activities that related with Exclusive Breastfeeding through counseling and Breastfeeding food demonstration to society, especially mothers, the knowledge of healthy and nutritious breastfeeding food for children. It was also suggested that Public Health Centers and Integrated Service Center should improve its activities on the importance of the golden period of 1000 days, especially for childbearing age women and pregnant women in order to reduce the risk of stunting.